Striatin is a novel modulator of cell adhesion - Lahav-Ariel, Lital; Hofmann, Ilse (The FASEB journal, 2019)
The adherens junctions (AJs) and tight junctions (TJs) provide critical adhesive contacts between neighboring epithelial cells and are crucial for epithelial adhesion, integrity, and barrier functions in a wide variety of tissues and organisms. The striatin protein family, which are part of the striatin interaction phosphatases and kinases complex, are multidomain scaffolding proteins that play important biologic roles. We have previously shown that striatin colocalizes with the tumor suppressor protein adenomatous polyposis coli in the TJs of epithelial cells. Here we show that striatin affects junction integrity and cell migration, probably through a mechanism that involves the adhesion molecule E-cadherin. Cells engaged in cell-cell adhesion expressed a high MW-modified form of striatin that forms stable associations with detergent-insoluble, membrane-bound cellular fractions. In addition, striatin has recently been suggested to be a target of the poly (ADP-ribose) polymerases Tankyrase 1, and we have found that striatin interacts with Tankyrase 1 and is subsequently poly-ADP-ribosylated. Taken together, our results suggest that striatin is a novel cell-cell junctional protein that functions to maintain correct cell adhesion and may have a role in establishing the relationship between AJs and TJs that is fundamental for epithelial cell-cell adhesion.—Lahav-Ariel, L., Caspi, M., Nadar-Ponniah, P. T., Zelikson, N., Hofmann, I., Hanson, K. K., Franke, W. W., Sklan, E. H., Avraham, K. B., Rosin-Arbesfeld, R. Striatin is a novel modulator of cell adhesion.